Growth and yield of soybean as influenced by maize + soybean intercropping systems and nitrogen levels - Singh, Jasbir; Thenua, O.V.S. (Annals of Agricultural Research, 2014)
A field investigation was conducted at Amar Singh College, Lakhaoti, Bulandshahr during kharif seasons of 2009 and 2010 to study the growth and yield performance of soybean under maize + soybean intercropping systems and nitrogen levels. Soybean grown as intercrop registered significantly higher growth and yield up to application of 40 kg N/ha to maize crop. The higher levels at 80 kg and 120 kg N/ha failed to produce significant effect. Similarly, the grain and stover yield showed significant improvement up to 80 kg N/ha. Increase in nitrogen upto 80 kg N/ha to maize crop did not show any adverse effect on soybean since except basal dose, the fertilizers were applied only to maize crop row zone. Maize + soybean intercropping led to efficient use of land and higher economic return. Interaction effect between cropping systems and N levels was not significant. The benefit : cost ratio was enhanced with maize + soybean intercropping in additive series and was superior as soybean improved the fertility status of soil.